The critical standard in the book Zad al-Tafsir wa Ghurra al-Muhayya The open literature of Abu Bahr Safwan bin Idris (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of all God’s creation, Muhammad bin Abdullah, the unlettered and trustworthy Arab prophet, and upon his pure and chaste family, and upon his honorable and chosen companions.And after:Authorship in Andalusia began with the books of classes early, that is, in the late third century of migration, and its authors were influenced by the books of advanced classes that entered Andalusia, and the Andalusian writers and poets had classes that did not reach us, such as the classes of writers in Andalusia by Muhammad bin Musa (d. (d. 457 AH) and many others.Linguistically, criticism: - criticism is different from the negative (), distinguishing the dirhams and removing the false ones from them; The dirhams are more valuable than their grasp, and the trees are more leafy ().Criticism idiomatically: Poetry criticism is a special work that can only be undertaken by those who have insight and experience in good or bad poetry, and that it is different from linguistic and grammatical work. Literary criticism has many cultural and historical connotations in national and international literatures, which are connotations that were created and colored by the nature of the literary experience itself, whether it was poetry or prose, when the literary experience became the source of human thought in its interaction with reality and in the creation of artistic and aesthetic relations developed from society ().Here, the term criticism enters into the heart of social change, as it becomes an important type of literary experience, and it is deeply rooted in the lofty human arts (), and Dr. Muhammad Ghoneimi Hilal says in his book (Modern Literary Criticism) (that criticism is a good distinction for silver or gold coin From its false, which necessitates experience, thought, then judgment (), which is the closest meaning to the etymological origin synonymous with criticism in European languages (criticism), and this word is taken from the Greek verb (kriein), meaning in the original judgment or thinking (), and literary criticism is a linguistic creation from another linguistic creation It is literature that uses the same tool that a subject uses, and shares with it the basic components.In fact, criticism is a worldly human activity (wordly), and it is the product of a social world that exerts its influence on it in a complex and effective manner at the same time, imprinting it with its social character that makes it closely related to the life of society. Which he produces in order to improve its various aspects through his search for the best, the best, and the highest in this life ().